THE CONSEQUENCES OF USING DIFFERENT VARIANTS OF IMPLEMENTATION OF REDISTRIBUTIVE PAYMENT – A CASE STUDY OF POLAND (Polityki Europejskie, Finanse i Marketing)
The article describes a diagnostic study measuring the degree of concentration of the aid which is currently distributed under the direct support system for farmers in Poland; it also presents the regional differentiation in aid concentration. The author conducted a simulation test quantifying the redistributive effects of applying various variants of an instrument equalising the amounts of support granted to farms. This can make the basis for an ex-ante assessment of alternative options of the implementation of redistributive payment. The research enabled the identification of ranges of the areas of farms which benefit from the current shape of redistributive payment and which may benefit from alternative variants given as examples. The final part of the article contains several recommendations on how to design redistributive payment at a national level, depending on the goals to be achieved with this instrument.